WORK MOTIVATION AND ORGANIZATIONAL CULTURE IN IMPROVING EMPLOYEE PERFORMANCE OF NATIONAL PRIMARY COOPERATIVE COMPANIES - Mohamad Sukri; Bambang Heru Purwanto; Rully Indrawan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of this study is to conduct an analysis towards the effect of work motivation partially on employee performance in cooperative companies, somewhat analyzing the influence of organizational culture on employee performance in suitable companies, knowing and analyzing the effect of work motivation and corporate culture simultaneously on employee performance in combined companies, and knowing and analyzing improvement strategies that should be carried out to improve employee performance in suitable companies, particularly those related to work motivation and organizational culture. The hypothesis proposed: There is a significant influence of work motivation on employee performance in suitable companies, There is a substantial influence of work culture on the performance of suitable company employees, There is an influence of work motivation and organizational culture jointly on the performance of employees of suitable companies. There is a formulation of research confirmation results. From the opinions of experts or experts judgment about improvement strategies in improving cooperative employees' performance, especially those related to work motivation and organizational culture. This study used mixed methods research design with a combination of sequential explanatory research objects of Astra International Cooperative and Benteng Mikro Syariah Cooperative. The research population was 1056, sampling determination using the Slovin formula as many as 290 respondents. This study states that work motivation and organizational culture are very influential in improving cooperative employees' performance. The partial motivation factor is quite significant in increasing employee performance. Likewise, the work culture factor influences improving performance, so both factors, both work motivation and organizational culture, substantially influence the performance of cooperative employees